Rise to the challenge or not give a damn: Differential performance in high vs. low stakes tests - Yigal Attali; Zvika Neeman; Analia Schlosser (Institute for the Study of Labor (IZA), 2011)
This paper studies how different demographic groups respond to incentives by comparing performance in the GRE examination in high and low stakes situations. The high stakes situation is the real GRE examination and the low stakes situation is a voluntary experimental section of the GRE that examinees were invited to take immediately after they finished the real GRE exam. We show that males exhibit a larger difference in performance between the high and low stakes examinations than females, and that Whites exhibit a larger difference in performance between the high and low stakes examinations relative to Asians, Blacks, and Hispanics. We find that the larger differential performance between high and low stakes tests among men and whites can be partially explained by the lower level of effort invested by these groups in the low stake test.
urn:nbn:de:101:1-201105173299
Keywords: J16; J24; I24; M52; 330; gender; competition; incentives; GRE; high stakes; low stakes; test score gap